Can water allocation in the Yellow River basin be improved? Insights from a multi-agent system model - Cai, Ximing; Yang, Yi-Chen E.; Jianshi, Zhao; Ringler, Claudia (International Food Policy Research Institute, 2011)
In 1999, the Government of China enforced a cross-provincial, quota-based Water Allocation Agreement that was developed in 1987 and titled Unified Water Flow Regulation (UWFR) to ensure that flow to the Yellow River mouth would not be cut off. This policy was in line with the refocus of the Government, over the last decade, on sustainable water use and keeping the Yellow River healthy. The policy enforcement ended more than two decades of flow-cutoffs, that is, periods when the Yellow River did not reach the Bohai Sea at its mouth, during an increasing number of days every year.